Improving Contrast Enhancement in Pulmonary CTA: The value of breathing maneuvers - Manava, P.; Galster, M.; Schoen, M.; Ficker, J.; Lell, Michael; Adamus, R.; Bruch, M. (European Journal of Radiology Open, 2020)
Purpose: To investigate contrast dynamics and artifacts associated with different breathing maneuvers during pulmonary computed tomography angiography (pCTA) in a prospective randomized clinical trial. Method: Three different breathing maneuvers (inspiration, expiration, Mueller) were randomly assigned to 146 patients receiving pCTA for suspected pulmonary embolism (PE). Contrast enhancement of central and peripheral arteries and imaging quality of lung parenchyma were compared and analyzed. Results were compared by using the analysis of variances (ANOVA) and Kruskal-Wallis-Test. Results: Mean enhancement in the pulmonary trunk was highest during breath-hold in inspiration (293 HU, range 195–460 HU) compared to Mueller (259 HU, range 136–429 HU, p = 0022) and expiration (267 HU, range 115–376 HU). This was similar for the right pulmonary artery (inspiration 289 HU, range 173–454 HU; Mueller 250 HU, range 119–378 HU; p = 0.007; expiration 257 HU, range 114–366 HU; p = 0.032) and left pulmonary artery (inspiration 280.3 HU, range 170–462 HU; Mueller 245 HU, range 111–371 HU; p = 0.016; expiration 252 HU, range 110–371 HU). Delineation of peripheral arteries was significantly better in inspiration vs Mueller (p = 0.006) and expiration (p = 0.049). Assessment of the lung parenchyma was significantly better in inspiration vs Mueller (p = 0.013) or expiration (p < 0.001). Conclusions: Resting inspiratory position achieved the highest enhancement levels in central and peripheral pulmonary arteries and best image quality of the pulmonary parenchyma in comparison to other breathing maneuvers. It is necessary to train the maneuver prior to the examination in order to avoid deep inspiration with the risk of suboptimal opacification of the pulmonary arteries.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Breathing; Computed tomography angiography; Contrast density; Image quality; Pulmonary arteries; Pulmonary embolism